Determination of Mechanical Properties of Plastic Components Made by 3D Printing - Sedlak, Josef; Joska, Zdenek; Hrbackova, Lucie; Jurickova, Eva; Hrusecka, Denisa; Horak, Ondrej (Manufacturing Technology Journal, 2023)
The presented article deals with the determination of selected mechanical properties of additive ma-terials used for 3D printing (PETG, PLA, ABS, ABS +, PLA ESD, ASA, PC / ABS). Due to the fact that 3D printing has exploded over recent years and additive manufacturing has become popular in some industries, the quality of input materials and their mechanical properties is extremely im-portant. We used 3D printer Original Prusa MK3 to prepare samples for testing. Individual samples printed from all above mentioned materials were analyzed using selected mechanical tests (static tensile test, hardness tests). In the static tensile test, selected parameters (tensile strength limit, ten-sile modulus, elongation) were determined for all additive samples, which were statistically pro-cessed. The parameters for two methods of measuring hardness were also statistically evaluated, namely Shore and ball indentation. All tested additive materials were compared with the aim of ob-taining the final ranking (point evaluation of tested materials with quantification of price costs). The best properties after the performed tests were achieved by the additive material PLA Filament Plasty Mladec.
Keywords: Aditive manufacturing; 3D printing; Fused filament fabrication; Mechanical properties; Tensile test